2016
DOI: 10.1051/0004-6361/201527726
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the SZ effect on cm-wavelength (1–30 GHz) observations of galaxy cluster radio relics

Abstract: Radio relics in galaxy clusters are believed to be associated with powerful shock fronts that originate during cluster mergers, and are a testbed for the acceleration of relativistic particles in the intracluster medium. Recently, radio relic observations have pushed into the cm-wavelength domain (1-30 GHz) where a break from the standard synchrotron power law spectrum has been found, most noticeably in the famous "Sausage" relic. Such spectral steepening is seen as an evidence for non-standard relic models, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 68 publications
4
63
0
Order By: Relevance
“…This also rules out a significant B-field variation within the CRE cooling time. The steepening found by Stroe et al (2016) for the Sausage and Toothbrush relics are based on two values at higher frequencies that, however, have large errors and may suffer from the SZ effect (Basu et al 2016). We note that the integrated flux densities of the Sausage and Toothbrush relics given in Table 4 of Stroe et al (2016) are based on the same maps as in this work, but are slightly different because the values in our Table 5 are obtained with somewhat different integration areas and an additional source subtraction in the case of the Toothbrush relic.…”
Section: Integrated Flux Densities and Spectral Indicesmentioning
confidence: 98%
“…This also rules out a significant B-field variation within the CRE cooling time. The steepening found by Stroe et al (2016) for the Sausage and Toothbrush relics are based on two values at higher frequencies that, however, have large errors and may suffer from the SZ effect (Basu et al 2016). We note that the integrated flux densities of the Sausage and Toothbrush relics given in Table 4 of Stroe et al (2016) are based on the same maps as in this work, but are slightly different because the values in our Table 5 are obtained with somewhat different integration areas and an additional source subtraction in the case of the Toothbrush relic.…”
Section: Integrated Flux Densities and Spectral Indicesmentioning
confidence: 98%
“…Basu et al (2016) showed that the Sunyaev-Zel'dovich (SZ) decrement in the observed radio flux can be significant above 10 GHz for radio relics. We adopt their estimates for the SZ contamination factor for the Toothbrush relic given in their Table 1.…”
Section: Volume-integrated Cre and Radio Spectramentioning
confidence: 99%
“…The error bars are given in the same tables. The solid black circles at 16 and 30 GHz are the data points, multiplied by factors of 1.1 and 1.8, respectively, which could represent the SZ-corrected fluxes (Basu et al 2016). electrons or preexisting soft-spectrum electrons, are accelerated by a strong shock with » M 3.0 s . The main results are summarized as follows: 1.…”
mentioning
confidence: 99%
“…5 (bottom panel). The fit suggests a narrow lognormal shape, with best-fit parameters [µ, σ] = [2.1, 0.9] kpc (see Basu et al 2016, Equation (9)), and a shock radius 882 kpc that is consistent with the SZ measurement. The observed broadening (Fig.…”
Section: Radio Modeling and The Relic B-fieldmentioning
confidence: 60%
“…The effective resolution is 6.1 × 3.1 , making the relic sufficiently resolved in the direction of shock propagation to fit a radial brightness profile. We use a lognormal emissivity model (Basu et al 2016) that is projected from a 3D cone and smoothed to the ATCA resolution. The fit is shown in Fig.…”
Section: Atca 21 Ghz Radio Datamentioning
confidence: 99%